2019
DOI: 10.1111/nyas.14290
|View full text |Cite
|
Sign up to set email alerts
|

How youth mentoring relationships end and why it matters: a mixed‐methods, multi‐informant study

Abstract: Scant empirical attention has been devoted to understanding endings in youth mentoring relationships, despite the frequency with which they occur. This study examined data from a mixed‐methods study of mentoring relationship endings in which youth mentees, the youth's parents or guardians, mentors, and program staff were surveyed about the closure process, and a subsample of program staff, mentors, and parents or guardians also participated in in‐depth qualitative interviews. Findings from a descriptive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Their reported reasons for early termination included genuinely unforeseen changes in the mentors’ and mentees’ life circumstances, mentees’ dissatisfaction, disappointment or disinterest, mentor dissatisfaction, unrealistic expectations on the part of the mentors or the mentees, the mentors’ lack of relational skills, parents’ interference and lack of parental support, gradual dissolution with neither party investing the effort to maintain the interaction, and mentors’ and mentees’ abandonment. Weaker relationships were more likely to end as a result of mentors’ or mentees’ dissatisfaction with the relationship, or to dissolve without formal termination [ 116 , 118 , 119 , 120 , 121 ]. Mentees’ avoidance, distrust, fear of intimacy and rejection, and mentors’ overwhelming derived from the mentees’ needs and difficulties discussing the termination of the relationship were noted as reasons for early termination in a short-term mentoring program for pregnant teens [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their reported reasons for early termination included genuinely unforeseen changes in the mentors’ and mentees’ life circumstances, mentees’ dissatisfaction, disappointment or disinterest, mentor dissatisfaction, unrealistic expectations on the part of the mentors or the mentees, the mentors’ lack of relational skills, parents’ interference and lack of parental support, gradual dissolution with neither party investing the effort to maintain the interaction, and mentors’ and mentees’ abandonment. Weaker relationships were more likely to end as a result of mentors’ or mentees’ dissatisfaction with the relationship, or to dissolve without formal termination [ 116 , 118 , 119 , 120 , 121 ]. Mentees’ avoidance, distrust, fear of intimacy and rejection, and mentors’ overwhelming derived from the mentees’ needs and difficulties discussing the termination of the relationship were noted as reasons for early termination in a short-term mentoring program for pregnant teens [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…A mixed-methods American study that collected data from parents, mentees, mentors, and program staff about the closure process indicated that the mentors initiated most relationship endings. In most cases, the endings were dissolved unexpectedly and unclearly, leaving parents to manage the closure with their child [ 121 ]. More quantitative studies are needed to better understand the causes and consequences of early termination of the mentoring relationship in the various formats (long, short, determined, or undetermined endpoints).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unclear or competing expectations can lessen the effectiveness of mentoring and cause participants to give up on the mentoring. [82][83][84] Effective mentoring relies on mentors and mentees having clear ideas about what mentoring entails, how it is distinct from other support measures, and what expectations for a given mentoring experience are realistic. 65,81,10 All stakeholders need to understand that mentoring is relational and developmental, has instrumental (e.g., careeroriented) and psychosocial functions, and includes phases and transitions in which mentoring roles will change.…”
Section: Key Issue 5: the Orchestration Of Mentoring Goals And Mentormentioning
confidence: 99%
“…The existence of multiple ill‐defined mentor roles is problematic in that it can exacerbate or even lead to unclear expectations about the mentoring. Unclear or competing expectations can lessen the effectiveness of mentoring and cause participants to give up on the mentoring 82–84 …”
Section: Seven Key Issues In Professionalizing Mentoring Practicesmentioning
confidence: 99%